Needs Analysis of Digital-Based Nanny Care Services to Improve the Quality of Maternal and Child Health Services - Pipit Festi Wiliyanarti; Rewina Intan Asmarani; Umi Ma'rifah (Universitas Muhammadiyah Surabaya, 2026)
High morbidity rate among mothers and children remains a significant issue requiring special attention. Nanny care is a professional caregiving service provided by trained individuals to care for children in the household. This research adopted a quantitative analytical design utilizing a cross-sectional methodology. The study population comprised all individuals who accessed maternal and child health services at a designated Mother and Child Hospital in the Surabaya region. A total of 50 respondents were selected through probability sampling employing a simple random technique. Data were collected using a modified version of the Family Needs Questionnaire. The sample specifically included mothers receiving antenatal and postnatal care services. Analytical procedures included frequency distributions and correlation analyses to examine the relationship between perceived care needs and the demand for nanny care services, employing the chi-square test with α = 0.05. There was a significant relationship between maternal and child care needs and the availability of support in nanny care services (p = 0.04, α = 0.05). In conclusion, Digital nanny services can be integrated into Maternal and Child Health (MCH) systems by connecting real-time monitoring, health education, and personalized support for mothers and children. This integration enhances early detection of health issues, improves care coordination, and supports data-driven decision-making within MCH programs.